Numerical and experimental analysis of electromagnetic field propagation for ground penetrating radar inspection - Rucka, Magdalena; Lachowicz, Jacek (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
This paper presents experimental tests by using the GPR method and numerical analysis of electromagnetic field propagation. The object of the experimental research was a ground floor structure. An antenna of frequency of emitted waves equal to 2 GHz was used for measurements. The paper also describes the numerical modelling of electromagnetic field with the use of the finite difference time domain method. Results of propagation of electromagnetic waves in a one-dimensional reinforced concrete specimen were presented.